Digital Communication: Bridge to Repurchase Intention - Batoteng, Hendrik; Surahman, Surahman; Barus, Bela; Patimah, Patimah; Batoteng, Gloria Adelaide; Aulia, Rahmah Athaya (International Journal Labs, 2023)
Background: According to the Top Brand Index (TBI) statistics for 2021, Milo was ranked fifth in the ready-to-drink liquid milk category. Furthermore, in the Milk Powder category, Milo was picked third out of four milk brands in the same year. Aim: This study examines the impact of Brand Familiarity, Brand Love, and e-WOM on Brand Attitude and the Repurchase Intention of Milo brand consumers in Samarinda City. Method: This study uses a questionnaire with the object of research being the Milo Brand product. The sample of this study is 147 respondents conducted in the city of Samarinda. The method of sampling is accidental sampling, which means that data were collected from respondents while found. The research methodology for this study involves using a quantitative approach, including path analysis and Structural Equation Modeling (SEM), which were analyzed using IBM SPSS Statistic 25 software and AMOS 5.0 software. Findings: The analysis of the structural model in this study found that three out of six hypotheses were significant: (1) the effects of Brand Familiarity, e-WOM, and Brand Love on Brand Attitude, and (2) the effects of e-WOM, Brand Love, and Brand Attitude on Repurchase Intention. The other three hypotheses were not significant: (1) the effect of Brand Familiarity on Brand Attitude, (2) the effect of Brand Love on Repurchase Intention, and (3) the effect of e-WOM on Repurchase Intention.